Development of 42-GHz, 200-kW gyrotron for indian tokamak system tested in the regime of short pulselength - Bera A.; Singh N.K.; Kumar N.; Rathi D.; Satynaryana K.; Singh U.; Kulkarni S.V.; Mishra A.K.; Vishant; Khatun H.; Alaria M.K.; Varia A.; Parmar K.; Kadia B.; Srinivas Y.S.S.; Kevadia M.; Ranjan O.; Pareek N.; Babu R.; Das S.; Jain P.K.; Sinha A.K.; Kartikeyan M.V.; Joshi S. (My University, 2025)
A 42-GHz, 200-kW gyrotron was developed and tested for the Indian plasma fusion system. The gyrotron was designed for the TE0,3 operating mode. The configuration of the triode-type magnetron injection gun (MIG) with the linear RF output, undepressed collector, and face-cooled double disk window was adopted in this gyrotron because of the first development experience. The complete tube was developed and processed at Central Electronics Engineering Research Institute (CEERI), Pilani, India. The RF testing of the gyrotron was performed at the participating institute, Institute of Plasma Research (IPR), Gandhinagar, India. Due to some cooling issues in the collector region, the tube was tested by a resistive capacitor network-based power supply for a very short pulse in place of a long pulse, high voltage power supply. The tube was tested up to the beam voltage of 51 kV and a beam current of 12 A at the cavity magnetic field of 1.61 T for the short pulse of 500μs. The tube was inserted into the magnet system consisting of a main electromagnet, auxiliary gun coils, and collector magnets. The multi-hole and single hole couplers were used to measure the RF power in the TE0,3 mode and the overall power, respectively. The measured results were also compared with the simulated results and a close agreement of the results was found. The short pulse testing confirms the electrical design and the development approach for the 42-GHz gyrotron tube. © 1973-2012 IEEE.